Generation of an inducible dCas9-SAM human PSC line for endogenous gene activation - Petazzi, Paolo; Gutierrez-Agüera, Francisco; Roca-Ho, Heleia; Castaño, Julio; Bueno, Clara; Alvarez, Niuska; Forrester, Lesley M.; Sevilla, Ana; Fidanza, Antonella; Menendez, Pablo (Frontiers in Cell and Developmental Biology, 2024)
The CRISPR/Cas9 system has transformed genome editing by enabling precise modifications for diverse applications. Recent advancements, including base editing and prime editing, have expanded its utility beyond conventional gene knock-out and knock-in strategies. Additionally, several catalytically dead Cas9 (dCas9) proteins fused to distinct activation domains have been developed to modulate endogenous gene expression when directed to their regulatory regions by specific single-guide RNAs. Here, we report the development of the H9 human pluripotent stem cell (hPSC) line expressing an inducible dCas9-SAM activator (H9-iCas9.SAM), designed to activate transcription of endogenous genes. The H9-iCas9.SAM cells were generated through targeted integration of an inducible CRISPR/Cas9-based gene activator cassette into the AAVS1 “safe-harbour” locus. Molecular analyses confirmed precise and specific integration, ensuring minimal off-target effects. Functional characterization revealed that H9-iCas9.SAM cells retain pluripotency and display inducible endogenous gene activation upon doxycycline treatment. The versatility of H9-iCas9.SAM cells was demonstrated in directed in vitro differentiation assays, yielding neural stem cells (ectoderm), hematopoietic progenitor cells (mesoderm), and hepatocytes (endoderm). This underscores their potential in developmental biology studies and cell therapy applications. The engineered H9-iCas9.SAM line provides a robust platform for investigating gene function and advancing next-generation cell-based therapies.